Vitamin D Receptor FokI Gene Polymorphism Predicted Poor Response to Treatment in Chronic HCV Genotype 4 - Hany Shehab (International Journal of Biomedicine, 2016)
The aim of this study was to investigate the association between a genetic polymorphism of the vitamin D receptor (VDR) and antiviral responses in Egyptian patients with chronic hepatitis C virus genotype 4 (HCV-4). Methods: Our study enrolled 100 HCV-4 patients who received pegylated interferon alpha-2a (pegIFNα-2a) and ribavirin for 48 weeks. Patients were divided into 2 groups according to their response to therapy: 50 were responders, and 50 were non-responders. All HCV-4 patients were further subjected to the following laboratory tests: HCV-RNA using quantitative PCR, vitamin D level using ELISA and VDR genotype using PCR-RFLP assays, and abdominal ultrasonography. Results: There was a statistically significant difference in the frequency of the VDR polymorphism (FokI rs10735810) between responders (FF: 60%, Ff: 16%, ff: 24%) and non-responders (FF: 10%, Ff: 26%, ff: 64%) (P<0.001). There was a statistically significant association between VDR polymorphism with higher ALT levels (ff: 63.2±30.8, Ff: 48.5±19.5, FF: 54.4±10.8 U/L, p=0.04) and higher alkaline phosphatase levels (ff: 102.6±53.2, Ff: 100.3±66.4, FF: 68.3±29.4 U/L, P=0.007). VDR polymorphism showed no association with baseline vitamin D levels (P=0.21). Conclusion: VDR polymorphism plays a role in the treatment response of HCV and the modification of disease progression in Egyptians infected with chronic HCV-4.